Hubungan Interaksi Sosial Siswa dengan Hasil Belajar IPS Siswa Kelas IV SD Negeri 01 Indralaya Selatan - Santika, Mira; Heldayani , Eni; Syaflin , Sylvia Lara (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Pahlawan Tuanku Tambusai, 2022)
This study aims to determine whether there is a relationship between student social interaction and social studies learning outcomes for fourth grade students at SD Negeri 01 Indralaya Selatan.This research is a type of quantitative research using the Pearson product moment correlation research method. The population in this study were all fourth grade students of SD Negeri 01 Indralaya Selatan who found 39 students.Sampling Techniques Researchusing sampling techniques obtained two classes, namely class IVA and IVB SD Negeri 01 Indralaya Selatan. Data collection techniques using questionnaires, observations, and data documentation. Testing the research hypothesis data using the independent sample t-test. The results based on the research indicate that there is positive and significant relationship between students' social interaction and social studies learning outcomes for students in grades IVA and IVB at SD Negeri 01 Indralaya Selatan.